Sex Differences in Tenure Profiles: Effects of Shared Firm-Specific Investment - Becker, Elizabeth; Lindsay, Cotton M. (Journal of Labor Economics, 1994)
This article employs a model of Masanori Hashimoto with extensions by Donald Parsons to analyze variation in tenure by sex, age, and firm type. Fixed-wage contracts eliminate postcontractual opportunism associated with firm-specific human capital investment. However, such contracts result in inefficient quits and terminations. Calibration of the sharing of this investment between workers and employers minimizes the costs of these inefficient separations. Moreover, this optimal sharing rate varies systematically with the characteristics listed above. These tenure-slope implications are tested with favorable results.